Imagining the Perfect Asian Woman Through Hate: Michelle Phan, Anti-Phandom, and Asian Diasporic Beauty Cultures. (15th May 2020) - Tran, Tony
Abstract: This article examines the predominately Asian American "Anti-Phandom" community on GuruGossiper.com to explore how anti-fans of YouTube star Michelle Phan engage with ideologies of beauty cultures within Asian diasporic contexts. For many, Anti-Phandom provides an online space where personal concerns about female Asian beauty standards can be negotiated through Michelle Phan. Within these conversations, I argue Anti-Phans display forms of resistance to Phan's postfeminist forms of female empowerment on racial and ethnic terms. However, these counters to Phan's notions of beauty also produce a rubric of the beautiful Asian woman which renders difference as ugly, creating idealized definitions of racial beauty and Asian/American cultures based on essentialized categories that police diasporic women.